Tokyo Vernacular : Common Spaces, Local Histories, Found Objects - Sand, Jordan, 1960- (University of California Press, 2013)
Preserved buildings and historic districts, museums and reconstructions have become an important part of the landscape of cities around the world. Beginning in the 1970s, Tokyo participated in this trend. However, repeated destruction and rapid redevelopment left the city with little building stock of recognized historical value. Late twentieth-century Tokyo thus presents an illuminating case of the emergence of a new sense of history in the city's physical environment, since it required both a shift in perceptions of value and a search for history in the margins and interstices of a rapidly modernizing cityscape.